2002
DOI: 10.1117/12.453707
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond optical studies of cuprates

Abstract: Femtosecond optical reflectivity measurements of La 2-x Sr x CuO 4 , La 2 CuO 4+y , Bi 2 Sr 2 CuO 6+z and Bi 2 Sr 2 CaCu 2 O 8+δ thin films and single crystal samples indicate qualitative changes with fluence. At the lowest fluencies, there is a power law divergence in the relaxation time. The divergence has an onset temperature of 55±15K, independent of whether the sample is in the superconducting or normal states. At slightly higher fluencies, still perturbative, the additional response does not exhibit this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
5
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 24 publications
6
5
1
Order By: Relevance
“…This is consistent with other pump-probe studies performed under low-fluence excitations. 13,14 Contrary to some earlier observations, 15,16 our data are fitted by a simple linear recombination model, and weak, damped oscillations on top of the exponential decay might, tentatively, be ascribed to displaced excitation of coherent acoustic phonons. 15,17 Overall, our observations for the pure YBCO film are in agreement with reported data 14,[18][19][20] and corroborate current interpretation that the slow dynamics below T c (several tens of picoseconds) cannot be ascribed to the acoustic phonon bottleneck, in contrast with the case of low-T c superconductors.…”
Section: Time-resolved Optical Response Of All-oxide Yba 2 Cu 3 O 7 contrasting
confidence: 99%
See 1 more Smart Citation
“…This is consistent with other pump-probe studies performed under low-fluence excitations. 13,14 Contrary to some earlier observations, 15,16 our data are fitted by a simple linear recombination model, and weak, damped oscillations on top of the exponential decay might, tentatively, be ascribed to displaced excitation of coherent acoustic phonons. 15,17 Overall, our observations for the pure YBCO film are in agreement with reported data 14,[18][19][20] and corroborate current interpretation that the slow dynamics below T c (several tens of picoseconds) cannot be ascribed to the acoustic phonon bottleneck, in contrast with the case of low-T c superconductors.…”
Section: Time-resolved Optical Response Of All-oxide Yba 2 Cu 3 O 7 contrasting
confidence: 99%
“…According to earlier studies on high-T c materials, 13 the amplitude of the DR/R signal grows below T c , while, simultaneously, the recovery becomes progressively slower. This is consistent with other pump-probe studies performed under low-fluence excitations.…”
Section: Time-resolved Optical Response Of All-oxide Yba 2 Cu 3 O 7 mentioning
confidence: 73%
“…But the leading terms are the same which are found in the case of metals in the above reference. The electron-phonon relaxation time follows T −3 law for cuprates which agrees well with the experimental results [2,3].…”
supporting
confidence: 88%
“…For that, it has been shown that the relaxation time follows the T −3 law [1] (T is phonon temperature) at low temperature (T e , T << T 0 ). The same evidence for relaxation time has also been reported experimentally for cuprates in low temperature region and it varies as T −(3±0.5) [2,3].…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation